Characterisation of a Natural Quartz Crystal as a Reference Material for Microanalytical Determination of Ti, Al, Li, Fe, Mn, Ga and Ge. Issue 2 (23rd October 2014) - Audétat, Andreas; Garbe‐Schönberg, Dieter; Kronz, Andreas; Pettke, Thomas; Rusk, Brian; Donovan, John J.; Lowers, Heather A.
<x xml:space="preserve">Abstract</x> A natural smoky quartz crystal from Shandong province, China, was characterised by laser ablation ICP‐MS, electron probe microanalysis (EPMA) and solution ICP‐MS to determine the concentration of twenty‐four trace and ultra trace elements. Our main focus was on Ti quantification because of the increased use of this element for titanium‐in‐quartz (TitaniQ) thermobarometry. Pieces of a uniform growth zone of 9 mm thickness within the quartz crystal were analysed in four different LA‐ICP‐MS laboratories, three EPMA laboratories and one solution‐ICP‐MS laboratory. The results reveal reproducible concentrations of Ti (57 ± 4 μg g−1), Al (154 ± 15 μg g−1), Li (30 ± 2 μg g−1), Fe (2.2 ± 0.3 μg g−1), Mn (0.34 ± 0.04 μg g−1), Ge (1.7 ± 0.2 μg g−1) and Ga (0.020 ± 0.002 μg g−1) and detectable, but less reproducible, concentrations of Be, B, Na, Cu, Zr, Sn and Pb. Concentrations of K, Ca, Sr, Mo, Ag, Sb, Ba and Au were below the limits of detection of all three techniques. The uncertainties on the average concentration determinations by multiple techniques and laboratories for Ti, Al, Li, Fe, Mn, Ga and Ge are low; hence, this quartz can serve as a reference material or a secondary reference material for microanalytical applications involving the quantification of trace elements in quartz.